Analysis of Predictive Risk Factors in Aquaporin-4-IgG Positive Highly Active Neuromyelitis Optica Spectrum Disorders - Li, Yanfei; Zhang, Jinwei; Zhou, Yongyan; Xie, Haojie; Duan, Ranran; Jing, Lijun; Yao, Yaobing; Teng, Junfang; Jia, Yanjie (Frontiers in Neurology, 2021)
Neuromyelitis optica spectrum disorders (NMOSDs) are inflammatory diseases with a high risk of recurrence and progressive disability, and it is crucial to find sensitive and reliable biomarkers for prognosis and the early prediction of relapse. Highly active NMOSD is defined as two or more clinical relapses within a 12-month period. In this study, we analyzed independent risk factors among patients with aquaporin-4 (AQP4)-IgG positive highly active NMOSD. In this retrospective study, we analyzed the data of 94 AQP4-IgG positive patients with highly active NMOSD and 105 AQP4-IgG positive controls with non-highly active NMOSD. In order to rule out possible effects of previous treatments (such as glucocorticoids, immunoglobulin, and immunosuppressants), we focused on the first-attack NMOSD patients admitted to our hospital. Clinical data, including the age of onset, gender, comorbidities, and serum analysis and cerebrospinal fluid (CSF) analysis results, were collected, after which logistic regression models were used to determine the associations between the clinical factors and relapse outcomes. The prevalence of connective tissue disease and the proportion of antinuclear antibody (ANA)-positivity were higher in the highly active NMOSD group than in the control group. The leukocyte counts, homocysteine (Hcy) levels, CSF leukocyte counts, protein concentrations, IgG indexes, and 24h IgG synthesis rates were also higher in the highly active NMOSD group. The results of multivariate analysis indicated that connective tissue disease comorbidity (OR = 5.953, 95% CI: 1.221–29.034, P = 0.027), Hcy levels (OR = 1.063, 95% CI: 1.003–1.126, P = 0.04), and 24h IgG synthesis rate (OR = 1.038, 95% CI: 1.003–1.075, P = 0.034) may be independent risk factors for AQP4-IgG positive highly active NMOSD relapse after adjusting for various variables. Comorbidity of connective tissue disease, Hcy levels, and 24h IgG synthesis rate may be independent risk factors for AQP4-IgG positive highly active NMOSD.